Talk is cheaper: bypassing the courts with win-win mediation - (:unkn) unknown (My University, 2016)
The article addresses the advantages of using an ADR Center to resolve different types of conflicts. The document makes mention of the Community Mediation Act of 1998, which created a new dispute resolution agency in Trinidad.